Incorporating self-compassion interventions in online bereavement support group for suicide loss survivors in Malaysia - Zien, Chin Yeng (2022)
Losing someone to suicide can be one of life’s most devastating experiences. In view of the pervasive stigma of suicide in Malaysia, interventions to address suicide grief has been inadequate, if not scarce. In addition to the insurmountable grief and pain, individuals bereaved by suicide are also at risk of detrimental mental health outcomes. Objectives This study evaluated the effectiveness of an online bereavement support group with self-compassion interventions on the mindfulness qualities, self-compassion, and grief reactions of suicide loss survivors in Malaysia. Method A total of four survivors participated in the eight-session online bereavement support group. Their levels of mindfulness qualities, self-compassion, and grief reactions were measured at pre- and post-intervention. Retrospective case analysis was also conducted to obtain anecdotal evidence of their subjective experience during the support group. Results A significant increase in overall mindfulness qualities and nonreactivity to inner experience and lower levels of isolation were observed after the intervention. Anecdotal evidence suggests an increased sense of belonging, increased knowledge on suicide bereavement, and increased intention and acceptance to practice self-compassion. Discussion The study contributes to the growing body of research on postvention and self-compassion. Practical implications are also highlighted to specific stakeholders, namely mental health clinicians, government agencies, non-government organizations, and the public. Conclusion Although further research is required, this study showcases the potential benefits of a selfcompassion- based support group on the subjective well-being of suicide loss survivors.